RELATIONSHIP BETWEEN STUDENT DIFFERENTIAL AND INTEGRAL CALCULUS LEARNING OUTCOMES TO STUDENT DIFFERENTIAL EQUATIONS LEARNING OUTCOMES - R.H. Yanti Silitonga (JME (Journal of Mathematics Education), 2023)
Differential and integral calculus courses are the foundations of mathematics that are important in understanding and applying differential equations. Students can take the Differential Equation course after graduating from theDifferential Calculus and Integral Calculus courses. This study aims to determine the relationship between understanding differential and integral calculus and students' learning outcomes of differential equations. The population in this study were all 2020 Pattimura University Teaching and Teacher Training Faculty Mathematics Education students who had takendifferential calculus, integral calculus, and differential equations courses, with a total sample of 33 people. The research method used is quantitative research with correlational methods. This study uses multiple regression analysis to findthe form and influence between the independent and dependent variables. Based on the results of the data analysis, it was concluded that there was a significant contribution between learning outcomes of differential calculus on learning outcomes of differential equations seen in the relative contribution of learning outcomes of differential calculus on learning outcomes of differential equations based on the calculation results obtained 56.45% while the relative contribution of learning outcomes of integral calculus 43 .54% of the learning outcomes of differential equations. So it shows a significant influence betweenlearning outcomes of differential and integral calculus on learning outcomes of differential equations.